Department Of Uzbek and Foreign Languages - Rakhmatilla Musurmanov (Western European Studies, 2024)
The article analyzes the specific features of the innovative educational cluster in modernized education, discusses guidelines for preventing and correcting students' negative attitude to classroom discipline, and gives recommendations.
Keywords: modernized education; innovative educational cluster; negative attitude to classroom discipline